2014
DOI: 10.11591/ijere.v3i3.6463
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of Structured Read-Aloud on Middle School Reading Achievement

Abstract: Read-aloud is a technique predominantly utilized at the elementary level. This study was designed to research the effectiveness of this technique at the middle school level, specifically, students who were not receiving special education or additional reading intervention services. For the current investigation, students in two middle schools within the same Virginia school district were assigned to receive the treatment of Structured Read-Aloud or received traditional middle-school reading instruction. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Reading aloud is argued to be most beneficial for children because it acts as the basis for their foundation to build knowledge 78-100 (Gurdon, 2019). During reading aloud, the teacher plays a crucial role to facilitate the interactions between the text and the students (Huang, 2010;Marchessault & Larwin, 2014). The following figure illustrates the role of the teacher in a reading-aloud activity.…”
Section: Reading Aloud: Definition Aspects and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reading aloud is argued to be most beneficial for children because it acts as the basis for their foundation to build knowledge 78-100 (Gurdon, 2019). During reading aloud, the teacher plays a crucial role to facilitate the interactions between the text and the students (Huang, 2010;Marchessault & Larwin, 2014). The following figure illustrates the role of the teacher in a reading-aloud activity.…”
Section: Reading Aloud: Definition Aspects and Characteristicsmentioning
confidence: 99%
“…The teacher's direct interaction with the text ensures that the teacher comprehends the text while acting to assess whether the text is suitable for the children. The teacher reads the text aloud to the children to create interaction between the children and the text (Huang, 2010), helping them understand the text without actually reading the text due to their early stage of competence (Marchessault & Larwin, 2014;Wadsworth, 2008). The teacher's voice will make the students focus on the text and the teacher's voice to avoid misunderstanding.…”
Section: Reading Aloud: Definition Aspects and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although scholars have promoted teacher read‐alouds beyond elementary school to foster reading engagement and enhance vocabulary and comprehension (Albright & Ariail, ), the practice has been underresearched. In an investigation of the effects of interactive read‐alouds on middle schoolers’ use of text to infer the meanings of unfamiliar words and search for answers to comprehension questions, Marchessault and Larwin () found that participants showed significant growth in both vocabulary and reading. The vocabulary assessment, however, involved matching a picture to a spoken word, testing only students’ receptive oral vocabulary skills, not their ability to infer word meanings from context, claimed to be one of the focal strategies in the study.…”
Section: Interactive Read‐alouds With Picture Booksmentioning
confidence: 99%